IMPROVING STUDENTS’ WRITING SKILL THROUGH SNOWBALL THROWING TECHNIQUE - PURNA WIRATNO; YOHANA PUSPITA DEWI; ADENAN DAMIRI; ENY DWI MARCELA (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2024)
This research has the aim to improve students' writing skill through Snowball Throwing Technique and determine whether its implementation increases students' learning activities. This research used a Classroom Action Research (CAR, there are both quantitative and qualitative data. The quantitative data was analyzed using the mean statistical formula, while the qualitative data was analyzed descriptively. The findings of improvement in students' learning activities, as indicated by the mean scores of students' learning activities in Cycle 1 (7.06) and Cycle 2 (7.81). Moreover, the writing test results showed an increase in the mean score from Cycle 1 (69.4) to Cycle 2 (79.5), with an improvement of 10.1 points. So, it can be concluded that the Snowball Throwing Technique can improve students' learning activities and writing skill at tenth-grade students of SMAN 8 Bandar Lampung in the academic year of 2023/2024.